Optically Stimulated Artificial Synapse Based on Layered Black Phosphorus. Issue 22 (24th April 2019) - Ahmed, Taimur; Kuriakose, Sruthi; Mayes, Edwin L. H.; Ramanathan, Rajesh; Bansal, Vipul; Bhaskaran, Madhu; Sriram, Sharath; Walia, Sumeet
Abstract: The translation of biological synapses onto a hardware platform is an important step toward the realization of brain‐inspired electronics. However, to mimic biological synapses, devices till‑date continue to rely on the need for simultaneously altering the polarity of an applied electric field or the output of these devices is photonic instead of an electrical synapse. As the next big step toward practical realization of optogenetics inspired circuits that exhibit fidelity and flexibility of biological synapses, optically‑stimulated synaptic devices without a need to apply polarity‑altering electric field are needed. Utilizing a unique photoresponse in black phosphorus (BP), here reported is an all‑optical pathway to emulate excitatory and inhibitory action potentials by exploiting oxidation‑related defects. These optical synapses are capable of imitating key neural functions such as psychological learning and forgetting, spatiotemporally correlated dynamic logic and Hebbian spike‑time dependent plasticity. These functionalities are also demonstrated on a flexible platform suitable for wearable electronics. Such low‐power consuming devices are highly attractive for deployment in neuromorphic architectures. The manifestation of cognition and spatiotemporal processing solely through optical stimuli provides an incredibly simple and powerful platform to emulate sophisticated neural functionalities such as associative sensory data processing and decision making. Abstract : Imitation of synaptic plasticity is the foundation for building optogenetics inspired electronics. By exploiting defects in black phosphorus, inhibitory and excitatory ion potentials are optically stimulated to mimic a range of sophisticated neural functionalities. The manifestation of cognition and spatiotemporal processing solely through optical stimuli offers an incredibly simple and powerful platform to emulate brain‐like associative learning and decision making.